2012
DOI: 10.1590/s0102-86502012000900002
|View full text |Cite
|
Sign up to set email alerts
|

Do opioid receptors play a role in the pathogenesis of the inflammatory response in acute pancreatitis?

Abstract: PURPOSE:To investigate the effect of the opioid blocker naltrexone in the inflammatory response in acute pancreatitis (AP). METHODS: Acute pancreatitis was induced in anesthetized male Wistar rats by retrograde injection of 2.5% sodium taurocholate diluted in 0.5ml saline into the main pancreatic duct. Animals were randomized to the following experimental groups: Control Group (n=9): animals received an intraperitoneal injection of saline solution (0.5ml), 15 minutes before the induction of AP. Naltrexone Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The pathogenesis of SAP remains poorly understood[ 21 ]. One hypothesis posits that inflammatory reactions are crucial for the pathogenesis of SAP[ 22 ]. Local inflammatory reactions in the pancreas lead to systemic inflammatory response syndrome (SIRS) and multiorgan failure (MOF), which is believed to be the primary cause of mortality[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of SAP remains poorly understood[ 21 ]. One hypothesis posits that inflammatory reactions are crucial for the pathogenesis of SAP[ 22 ]. Local inflammatory reactions in the pancreas lead to systemic inflammatory response syndrome (SIRS) and multiorgan failure (MOF), which is believed to be the primary cause of mortality[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, morphine therapy worsened the severity of AP and impeded resolution and regeneration of the pancreas ( Barlass et al, 2018 ), whereas another study indicated that morphine decreased vacuolization in edematous AP ( Bálint et al, 2022 ). Additionally, the opioid blocker naltrexone did not affect the pancreatic pathology and the inflammatory response ( Penido et al, 2012 ).…”
Section: Other Important Mediators Of Painmentioning
confidence: 99%